Women Entrepreneurs and Startups: Breaking Barriers - Mallepally, Akanksha; Mallepally, Ashritha (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The rise of women entrepreneurs marks a transformative shift in the global start-up ecosystem. Women-led start-ups are not only fostering innovation and economic growth but also promoting diversity and social change. However, women continue to encounter significant barriers, including limited access to funding, gender biases, networking challenges, and work-life balance pressures. This paper explores the evolving role of women entrepreneurs, analyses the obstacles they face, and highlights success stories that serve as beacons of inspiration. By addressing these barriers through supportive policies, mentorship, and inclusive investment practices, the entrepreneurial landscape can become more equitable and dynamic. Empowering women entrepreneurs is essential for building a sustainable and inclusive economy.